Early Specialization in Youth Sport: a requirement for adult expertise? - Baker, J. (High Ability Studies, 2003)
The role of early specialization in the development of sport expertise is a point of contention among researchers. While there is consistent evidence linking quantity of training with level of proficiency attained, a focus on specialized training during early stages of development has been linked with several negative consequences. Diversified involvement in a number of sports during early stages of development has been presented as a possible alternative to early specialization. Considering the consequences of advocating the early specialization approach and research suggesting the effectiveness of early diversification, coaches and sport scientists should consider the early diversification approach as an alternative. Further research is required to expand our understanding of the relative contributions of diversified versus specialized training.